Permanent Supportive Housing With Housing First to Reduce Homelessness and Promote Health Among Homeless Populations With Disability: A Community Guide Systematic Review. Issue 5 (September 2020) - Peng, Yinan; Hahn, Robert A.; Finnie, Ramona K. C.; Cobb, Jamaicia; Williams, Samantha P.; Fielding, Jonathan E.; Johnson, Robert L.; Montgomery, Ann Elizabeth; Schwartz, Alex F.; Muntaner, Carles; Garrison, Veronica Helms; Jean-Francois, Beda; et al.
Abstract : Context: Poor physical and mental health and substance use disorder can be causes and consequences of homelessness. Approximately 2.1 million persons per year in the United States experience homelessness. People experiencing homelessness have high rates of emergency department use, hospitalization, substance use treatment, social services use, arrest, and incarceration. Objectives: A standard approach to treating homeless persons with a disability is called Treatment First, requiring clients be "housing ready"—that is, in psychiatric treatment and substance-free—before and while receiving permanent housing. A more recent approach, Housing First, provides permanent housing and health, mental health, and other supportive services without requiring clients to be housing ready. To determine the relative effectiveness of these approaches, this systematic review compared the effects of both approaches on housing stability, health outcomes, and health care utilization among persons with disabilities experiencing homelessness. Design: A systematic search (database inception to February 2018) was conducted using 8 databases with terms such as "housing first, " "treatment first, " and "supportive housing." Reference lists of included studies were also searched. Study design and threats to validity were assessed using Community Guide methods. Medians were calculated when appropriate. Eligibility Criteria: Studies were included if they assessed Housing First programs in high-income nations, had concurrent comparison populations, assessed outcomes of interest, and were written in English and published in peer-reviewed journals or government reports. Main Outcome Measures: Housing stability, physical and mental health outcomes, and health care utilization. Results: Twenty-six studies in the United States and Canada met inclusion criteria. Compared with Treatment First, Housing First programs decreased homelessness by 88% and improved housing stability by 41%. For clients living with HIV infection, Housing First programs reduced homelessness by 37%, viral load by 22%, depression by 13%, emergency departments use by 41%, hospitalization by 36%, and mortality by 37%. Conclusions: Housing First programs improved housing stability and reduced homelessness more effectively than Treatment First programs. In addition, Housing First programs showed health benefits and reduced health services use. Health care systems that serve homeless patients may promote their health and well-being by linking them with effective housing services. Abstract : Supplemental Digital Content is Available in the Text.